Genetic enhancement : a solution to Singapore’s inequitable education system - Sabrina Abdullah@Ashley Boey Ching Wern (2019)
This essay seeks to argue that the Singapore education system is inequitable because of existing social inequalities, and genetic enhancement is permissible as one way of solving this inequality. In order to prove my thesis, I will justify that Singapore education system is indeed inequitable because there exists a myth of meritocracy. I will then look at arguments over the moral status of GE, issues of justice related to GE. I conclude that GE can and should be used to improve inequalities. I will also mention how GE can be used to solve inequalities in Singapore’s education system, while highlighting ways of regulating GE in Singapore. Albeit controversial, this is a new perspective that is unlike, but not incompatible with, other social approaches that attempt to address the social inequalities underpinning the Singapore education system.